R&D AND ECONOMIC GROWTH IN A CASH‐IN‐ADVANCE ECONOMY. (May 2014) - Chu, Angus C.; Cozzi, Guido
<x xml:space="preserve">Abstract</x> R&D investment has well‐known liquidity problems, with potentially important consequences. In this study, we analyze the effects of monetary policy on economic growth and social welfare in a Schumpeterian growth model with cash‐in‐advance (CIA) constraints on R&D investment, consumption, and manufacturing. Our main results can be summarized as follows. Under the CIA constraints on R&D and consumption (the CIA constraint on manufacturing), an increase in the nominal interest rate decreases (increases) R&D and economic growth. We also analyze the optimality of Friedman rule and find that Friedman rule can be suboptimal due to a unique feature of the Schumpeterian model.